2019
DOI: 10.1002/eat.23140
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and correlates of eating disorders in adult emergency department patients

Abstract: Objective This study describes the prevalence of eating disorders among adult patients who present to the emergency department for medical care and examines the relationship between eating disorders, depression, and substance use disorders. Method Emergency department patients aged 21–65 years (n = 1,795) completed a computerized questionnaire that included validated screening tools for eating disorders, risky drinking behavior, other substance use, and depression. Analyses were conducted comparing individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 58 publications
2
11
0
Order By: Relevance
“… 26 This is consistent with Dooley-Hash et al., who found an association between eating disorders and depression in females. 27 Moreover, our study is consistent with Alwosaifer et al., 14 who found no significant association between monthly family income and BMI.…”
Section: Discussionsupporting
confidence: 92%
“… 26 This is consistent with Dooley-Hash et al., who found an association between eating disorders and depression in females. 27 Moreover, our study is consistent with Alwosaifer et al., 14 who found no significant association between monthly family income and BMI.…”
Section: Discussionsupporting
confidence: 92%
“…Comprehensive treatment and prospective management of patients with eating disorders does not occur in the Emergency Department, however, EM clinicians can draw from guidelines to develop hospital admission criteria and/or provide follow-up referrals. Knowledge of guidelines and follow-up treatment options are critical as recent studies suggest 15.9% of adult participants screened positive for an eating disorder in the Emergency Department [ 13 ] and 16% of adolescent and young adults screened positive for an eating disorder in an Emergency Department [ 14 ]. One study of Australian EM, general, pediatric, and psychiatric clinicians reported previous knowledge of the 2014 Royal Australian and New Zealand College of Psychiatrists clinical practice guidelines for the treatment of eating disorders was related to increased confidence in treating eating disorders [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Detected prevalence of EDs among patients seeking emergency department services in the US was 16% and did not differ by reason for seeking treatment or any socio-demographic factors. Dooley-Hash et al [ 60 ] indicated this was much higher than the estimated prevalence in the general population (5%) and suggested that emergency department presentation could represent an important step in the identification of patients with ED for referral to services [ 60 ].…”
Section: Screeningmentioning
confidence: 99%